Enhancing Preschool English Vocabulary Through Multimedia Tools: Insights from a Mixed-Methods Study - Ilham, Muhammad; Rahman, Fadhlur; Sari, Dwhy Dinda; Annisaturrahmi, Annisaturrahmi (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – The primary objective of this research was to evaluate the effectiveness of multimedia tools in augmenting English vocabulary enrichment in preschool environments. This study was driven by the need to explore innovative approaches in early childhood language education and assess these tools' impact in enhancing learning experiences. Design/methods/approach – Adopting a mixed-methods approach, the study, conducted in two North Aceh preschools, evaluated multimedia integration in teaching and its impact on student outcomes, motivation, and engagement. It combined observations, document analysis, interviews, and tests, employing qualitative (educator interviews) and quantitative (vocabulary pre-and post-tests) data collection methods. Findings – The findings significantly improved students' vocabulary acquisition and active participation. Using multimedia tools in teaching and incredibly interactive PowerPoint presentations led to enhanced engagement and effectiveness in learning. Students showed marked improvements in self-confidence and language skills. The study also observed that multimedia integration fostered collaborative learning and increased technological proficiency among students. Research implications/limitations – These findings imply a potential paradigm shift in early childhood language education, suggesting incorporating multimedia tools for more engaging and compelling learning experiences. The study's limitations include its focus on specific preschool environments and the potential challenge of replicating the approach in resource-limited settings. Further research is needed to assess the approach's applicability in diverse educational contexts and its long-term impacts. Originality/value – This study offers novel insights into the application of multimedia tools in early childhood language education. It highlights how innovative teaching methods can significantly improve vocabulary skills and educational outcomes. These findings suggest impactful changes in teaching practices and pave the way for future research and potential shifts in educational policies. Paper Type Research paper